Implementasi Manajemen Berbasis Madrasah Dalam Peningkatan Mutu Pendidikan Di Madrasah - Karseno Handoyo; Mudhofir Mudhofir; Maslamah Maslamah (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study was to explore the uniqueness of the implementation of School Based Management (MBS) in Madrasahs. Madrasah education is interesting to study because after Pesantren, Madrasah became a reference for Islamic schools, which are formal schools with modern Islamic ideas. However, Madrasahs also have various problems related to quality and quality, both input and process and output. Using data from Madrasah Ibtidaiyah Negeri (MIN) 2 Sukoharjo and Madrasah Ibtidaiyah Negeri (MIN) 4 Sukoharjo, researchers will compare how the implementation of SBM in each Madrasah. Data collection techniques using interviews, documentation and field observations. The analysis technique used in the research is phenomenology, where the researcher tries to reveal the reality and experiences experienced by the individual, to understand something that is not visible from the individual's subjective experience. Researchers will go directly to the field, describe and construct existing realities and make approaches to information sources, so that it is hoped that the data obtained will be maximized. The research subjects were the principals of Madrasah Ibtidaiyah Negeri (MIN) 2 Sukoharjo and Madrasah Ibtidaiyah Negeri (MIN) 4 Sukoharjo, while the informants in this study were Deputy Heads, Administration, Teachers, Employees, Head of the Ministry of Religion of Sukoharjo Regency, Kasi who could provide information. about SBM policies, stakeholders and parents. The results of the research on the Concept of School-Based Sharia Management (MBS) implemented in Madrasah Ibtidaiyah Negeri 2 Sukoharjo and Madrasah Ibtidaiyah Negeri (MIN) 4 Sukoharjo are good enough. Some of the components in the SBM concept can be implemented well, such as the democratic leadership of the principal, the principal has been able to carry out the roles of educators, managers, leaders, administrators, supervisors, innovators and motivators well. In addition, the active role of the community has also been It seems that this can be seen with the assistance given to MIN 2 Sukoharjo and MIN 4 Sukoharjo both material and non-material.